The clinical efficacy of two semi-quantitative wound-swabbing techniques in identifying the causative organism(s) in infected cutaneous wounds - Angel, D.; Lloyd, P.; Carville, Keryln; Santamaria, Nick (Wiley-Blackwell Publishing Ltd, 2011)
A prospective randomised controlled trial of two paired wound-swabbing techniques (Levine versus Z) wasconducted to establish which method was more effective in determining the presence of bacteria in clinicallyinfected wounds. The Levine technique involves rotating the wound swab over a 1-cm2 area of the wound; the Ztechnique involves rotating the swab between the fingers in a zigzag fashion across the wound without touching thewound edge. Fifty patients were recruited into the study with acute (42%) and chronic wounds (58%). Overall, theLevine technique detected significantly more organisms than the Z technique (P = 0·001). When acute and chronicwounds were analysed separately, the Levine technique again detected more organisms in both acute (P = 0·001)and chronic wounds (P = 0·001). We conclude that the Levine technique is superior to the Z technique and thisresult may be because of the Levine technique’s ability to express fluid from the wound bed and thereby samplinga greater concentration of microorganisms from both the surface and slightly below the surface of the wound.